2007
DOI: 10.1002/jcc.20555
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the vertical excited states of benzene, pyrimidine, and pyrazine by the symmetry adapted cluster—Configuration interaction method

Abstract: The ground state and the excited states of benzene, pyrimidine, and pyrazine have been examined by using the symmetry adapted cluster-configuration interaction (SAC-CI) method. Detailed characterizations and the structures of the absorption peaks in the vacuum ultraviolet (VUV), low energy electron impact (LEEI), and electron energy loss (EEL) spectra were theoretically clarified by calculating the excitation energy and the oscillator strength for each excited state. We show that SAC-CI has the power to well r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 54 publications
(31 reference statements)
10
48
0
Order By: Relevance
“…These spectral assignments are supported by theoretical calculations based on time-dependent density functional theory 22 and the symmetry-adapted cluster configuration interaction method. 25 This behaviour is similar to that observed in the present electron energy loss spectra (see Fig. 1), where we find six spectral features.…”
Section: Physical Properties and Excited Electronic State Spectrosupporting
confidence: 91%
See 1 more Smart Citation
“…These spectral assignments are supported by theoretical calculations based on time-dependent density functional theory 22 and the symmetry-adapted cluster configuration interaction method. 25 This behaviour is similar to that observed in the present electron energy loss spectra (see Fig. 1), where we find six spectral features.…”
Section: Physical Properties and Excited Electronic State Spectrosupporting
confidence: 91%
“…These experiments have been interpreted with the assistance of numerous theoretical calculations to provide a detailed understanding of the singlet electronic states. [22][23][24][25][26] The pyrimidine photo-absorption spectrum is dominated by three broad features attributed to strong dipole-allowed transitions at 5.2, 6.7, and 7.6 eV. Specifically, the bulk of the intensity observed for these features has been assigned to π -π * transitions to the 1 B 2 , 1 A 1 , and 1 A 1 + 1 B 2 symmetry states, respectively.…”
Section: Physical Properties and Excited Electronic State Spectromentioning
confidence: 99%
“…Note that the respective positions and widths of the Gaussian functions for each inelastic feature were established through consideration of the experimental photo-absorption spectra, previous electron energy loss spectra, and calculated electronic excitation energies. 17,[28][29][30][31] The ratio of the area under the fitting function for the ith inelastic scattering feature to that found under the elastic feature determines the intensity ratio I i I 0 at that incident energy and scattering angle. The absolute differential cross sections for the inelastic processes contributing to the ith feature, dσ i0 d (E 0 , θ), can then be determined through…”
Section: Experimental Methods and Analysis Techniquementioning
confidence: 99%
“…See text for further details. combined with the theoretical calculations described above, sophisticated calculations from the literature and other experimental results 17,18,[28][29][30] to determine the states that contribute to the cross sections at specific energy loss values (see Sec. III).…”
Section: Inelastic Cross Sectionsmentioning
confidence: 99%
“…[32][33][34][35][36] The latter provide a basis for the description of the electronic excited states in our scattering calculations. These studies have reported that most of these states are valence in character with the exception of perhaps just four higher-lying (found in calculations above 7 eV) Rydberg singlet states 32 and a diffuse 3 B 2u (Ref.…”
Section: The Calculations Of Winstead and Mckoy Found Evidence Formentioning
confidence: 99%